2015
DOI: 10.1590/1677-5449.0008
|View full text |Cite
|
Sign up to set email alerts
|

Influência do diabetes mellitus sobre a perviedade da fístula arteriovenosa para hemodiálise

Abstract: ResumoContextoA incapacidade das fístulas arteriovenosas (FAVs) atenderem aos quesitos mínimos para realização da hemodiálise (HD) corresponde a uma das maiores causas de morbidade nos pacientes em terapia renal substitutiva. Identificar os fatores de risco associados com a falência do acesso vascular é fundamental para o manejo e sucesso da terapia hemodialítica.ObjetivoComparar o tempo médio de patência e a sobrevida das fístulas arteriovenosas realizadas nos pacientes portadores de diabetes mellitus com pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…13 Diabetes has been associated with poor AVF results, and lower blood flow, probably due to its influence on accelerating atherosclerosis progression on distal arteries. 8 , 22 , 25 In our series, these factors had no significant influence on AVF outcome.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…13 Diabetes has been associated with poor AVF results, and lower blood flow, probably due to its influence on accelerating atherosclerosis progression on distal arteries. 8 , 22 , 25 In our series, these factors had no significant influence on AVF outcome.…”
Section: Discussionmentioning
confidence: 47%
“…In the literature, female gender, increasing age, and diabetes mellitus are related to poor results. 6 , 8 , 23 , 24 Jemcov et al found that females had smaller arteries and that radial-cephalic AVF took longer to mature in women, but they had higher venous access flow compared to men. 13 Diabetes has been associated with poor AVF results, and lower blood flow, probably due to its influence on accelerating atherosclerosis progression on distal arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have demonstrated that the presence of diabetes increases the risk of AVF failure [11,[28][29][30][31]. Park et al [28] identified in the Cox proportional hazard model analysis that diabetes is an independent risk factor of primary patency (HR: 2.008, p = 0.043) in a cohort of 383 autogenous AVF.…”
Section: Discussionmentioning
confidence: 99%
“…Logo, é importante que esse acesso seja calibroso e tenha bom fluxo de sangue, permitindo a saída e o retorno sanguíneo entre o aparelho e o organismo, e que a FAV permita sessão dialítica por horas e tolere a punção frequente. Ressalta-se que este acesso é um recurso terapêutico utilizado pelos pacientes com IRC por toda a vida ou até que eles sejam submetidos a um transplante renal com resultados satisfatórios (DA CRUZ et al, 2015;FERNANDES et al, 2018).…”
Section: Discussionunclassified